2020
DOI: 10.21203/rs.2.17037/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early discontinuation of empirical antibiotic treatment in neutropenic patients with acute myeloid leukaemia and high-risk myelodysplastic syndrome

Abstract: Introduction: Current guidelines advocate empirical antibiotic treatment (EAT) in haematological patients with febrile neutropenia. However, the optimal duration of EAT is unknown. In 2011, we have introduced a protocol, promoting discontinuation of carbapenems as EAT after three days in most patients and discouraging the standard use of vancomycin as EAT.[NF1] This study assesses the effect of this protocol on carbapenem and vancomycine use in high risk haematological patients and its safety.Methods: A retro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Most published studies are retrospective or prospective observational, and the de-escalation and continuation arms are often not well matched (Table 1). Within the limitations of these studies, most found similar outcomes including rates of ICU admission and mortality in the de-escalation arm to the continuing antibiotic arm [61,62,[77][78][79][80][81]. Some reduction in carbapenems and vancomycin use has also been shown [77,79].…”
Section: Early De-escalation Of Therapy To Fluoroquinolone Prophylaxi...mentioning
confidence: 86%
See 1 more Smart Citation
“…Most published studies are retrospective or prospective observational, and the de-escalation and continuation arms are often not well matched (Table 1). Within the limitations of these studies, most found similar outcomes including rates of ICU admission and mortality in the de-escalation arm to the continuing antibiotic arm [61,62,[77][78][79][80][81]. Some reduction in carbapenems and vancomycin use has also been shown [77,79].…”
Section: Early De-escalation Of Therapy To Fluoroquinolone Prophylaxi...mentioning
confidence: 86%
“…Within the limitations of these studies, most found similar outcomes including rates of ICU admission and mortality in the de-escalation arm to the continuing antibiotic arm [61,62,[77][78][79][80][81]. Some reduction in carbapenems and vancomycin use has also been shown [77,79].…”
Section: Early De-escalation Of Therapy To Fluoroquinolone Prophylaxi...mentioning
confidence: 86%
“…Table 4 summarizes the most common complications observed with these therapeutic modalities and the current standards for their management. 90,91,110,[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] Targeted Therapeutic-Related Complications Targeted therapies represent the subclass of antineoplastic agents deliberately engineered to interfere with oncogenic signal transduction pathways and are divided into smallmolecule inhibitors, monoclonal antibody-based pharmaceuticals, and cell-based agents. In general, targeted agents are less toxic than nonspecific cytotoxic chemotherapeutics; however, because many agents require long-term use, both acute and chronic treatment-related toxicities should be considered (Fig.…”
Section: Table 3 (Continued)mentioning
confidence: 99%
“…• Vancomycin, linezolid, or daptomycin should be given only when either methicillin-resistant Staphylococcus aureus or indwelling catheter infections are likely and should be discontinued once these are ruled out (Niessen 2020 118 ).…”
Section: Table 3 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation